Hydrogen storage systems from waste Mg alloys - Pistidda, C.; Bergemann, N.; Wurr, J.; Rzeszutek, A.; Moller, Kasper; Hansen, B.; Garroni, S.; Horstmann, C.; Milanese, C.; Girella, A.; Metz, O.; Taube, K.; et al. (Elsevier SA, 2014)
The production cost of materials for hydrogen storage is one of the major issues to be addressed in order to consider them suitable for large scale applications. In the last decades several authors reported on the hydrogen sorption properties of Mg and Mg-based systems. In this work magnesium industrial wastes of AZ91 alloy and Mg-10 wt.% Gd alloy are used for the production of hydrogen storage materials. The hydrogen sorption properties of the alloys were investigated by means of volumetric technique, in situ synchrotron radiation powder X-ray diffraction (SR-PXD) and calorimetric methods. The measured reversible hydrogen storage capacity for the alloys AZ91 and Mg-10 wt.% Gd are 4.2 and 5.8 wt.%, respectively. For the Mg-10 wt.% Gd alloy, the hydrogenated product was also successfully used as starting reactant for the synthesis of Mg(NH2)2 and as MgH2 substitute in the Reactive Hydride Composite (RHC) 2LiBH4 + MgH 2. The results of this work demonstrate the concrete possibility to use Mg alloy wastes for hydrogen storage purposes. © 2014 Elsevier B.V. All rights reserved.